Горизонтальне вирівнювання місцевих бюджетів Причорноморського регіону : емпірична оцінка - Бойко, Світлана Василівна; Гошовська, Валентина Василівна (My University, 2019)
У статті розкрито особливості забезпечення системи вирівнювання місцевих бюджетів у контексті реалізації політики децентралізації та посилення територіальних асиметрій фінансового забезпечення в Україні. Метою статті є емпірична оцінка горизонтального вирівнювання місцевих бюджетів Причорноморського регіону. Проаналізовано загальний стан формування бюджетних ресурсів Причорноморського регіону за даними зведених обласних бюджетів; проведено оцінку горизонтального вирівнювання за видами місцевих бюджетів. На основі емпіричної оцінки горизонтального вирівнювання місцевих бюджетів Причорноморського регіону виявлено його диференціацію на основі диференціацію фіскального потенціалу за податком на доходи фізичних осіб та податком на прибуток підприємств. Високий рівень фіскального потенціалу виявлено у Одеській області, середній – Миколаївській області, низький – Херсонській області, що підтверджується значеннями та динамікою доходів зведених бюджетів областей, частки офіційних трансфертів у доходах зведених бюджетів областей, індексу податкоспроможності за надходженнями податку на прибуток підприємств обласних бюджетів, індекс податкоспроможності за надходженнями податку на доходи фізичних осіб різних видів бюджетів. In the article, there is analyzed the essence of horizontal equalization of local budgets in the context of the implementation of the policy of decentralization and strengthening the territorial asymmetries of financial support in Ukraine.The purpose of the article is empirical evaluation of the horizontal equalization of the local budgets of Black Sea region.The study of horizontal equalization of the local budgets of Black Sea region implemented in the following sequence: 1) evaluation of the general state of formation of budget resources of Black Sea region according to the consolidated regional budgets; 2) evaluation of horizontal equalization by type of local budgets. The econometric model of the dependence of the horizontal equalization of regional budgets and two variables (the index of taxpayability of income tax and the index of taxpayability of personal income tax) are built. The change in index of taxpayability of personal income tax by 1% was the result to an increase in the horizontal equalization by UAH 1.21 million, the index of taxpayability of income tax by 1% was the result to an increase in the horizontal equalization by UAH 0.43 million. Differentiation of horizontal equalization of the local budgets of Black Sea region on the basis of differentiation of fiscal potential of personal income tax and corporate income tax is discovered. High level of fiscal potential in Odesa region, middle level – Mykolayiv region, low level – Kherson region is discovered. This is confirmed by the values and dynamics of the revenues of the consolidated budgets of the regions, the share of official transfers in the revenues of the consolidated budgets of the regions, the index of taxpayability of income tax of regional budgets, the index of taxpayability of personal income tax of different types of budgets.
Keywords: горизонтальне вирівнювання; дотація; доходи бюджету; місцеві бюджети; horizontal equalization; subsidy; budget revenues; local budgets; кафедра фінансів